Mental imagery as a "motivational amplifier" to promote activities. (March 2019) - Renner, Fritz; Murphy, Fionnuala C.; Ji, Julie L.; Manly, Tom; Holmes, Emily A.
Abstract: Facilitating engagement in rewarding activities is a key treatment target in depression. Mental imagery can increase engagement in planned behaviours, potentially due to its special role in representing emotionally salient experiences. The present study tested the hypothesis that mental imagery promotes motivation and engagement when planning pleasant and rewarding activities. Participants were recruited from a community volunteer panel ( N  = 72). They self-nominated six activities to complete over the following week, and were randomized to either: a) a single-session Motivational Imagery condition ( N  = 24); b) an Activity Reminder control condition ( N  = 24); or c) a No-Reminder control condition ( N  = 24). As predicted, relative to control groups, the Motivational Imagery group reported higher levels of motivation, anticipated pleasure, and anticipated reward for the planned activities. The Motivational Imagery group also completed significantly more activities than the Activity Reminder group, but not more than the No-Reminder group. Relevance of results to behavioural activation approaches for depression are discussed. Highlights: Mental imagery of planned activities increases motivation to engage in them. Higher imagery vividness is associated with higher anticipated reward. Mental imagery of planned activities is associated with higher activity completion.